Characteristics, Treatment, and Health Care Expenditures of Medicare Supplemental‐Insured Patients with Painful Diabetic Peripheral Neuropathy, Post‐Herpetic Neuralgia, or Fibromyalgia. Issue 4 (16th January 2014) - Johnston, Stephen S.; Udall, Margarita; Alvir, Jose; McMorrow, Donna; Fowler, Robert; Mullins, Daniel
Abstract Objective To describe the characteristics, treatment, and health care expenditures of Medicare Supplemental‐insured patients with painful diabetic peripheral neuropathy (pDPN), post‐herpetic neuralgia (PHN), or fibromyalgia. Design Retrospective cohort study. Setting United States clinical practice, as reflected within a database comprising administrative claims from 2.3 million older adults participating in Medicare supplemental insurance programs. Subjects Selected patients were aged ≥65 years, continuously enrolled in medical and prescription benefits throughout years 2008 and 2009, and had ≥1 medical claim with an International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code for DPN, PHN, or fibromyalgia, followed within 60 days by a medication or pain intervention procedure used in treating pDPN, PHN, or fibromyalgia during 2008–2009. Outcome Measures Utilization of, and expenditures on, pain‐related and all‐cause pharmacotherapy and medical interventions in 2009. Results The study included 25, 716 patients with pDPN (mean age 75.2 years, 51.2% female), 4, 712 patients with PHN (mean age 77.7 years, 63.9% female), and 25, 246 patients with fibromyalgia (mean age 74.4 years, 73.0% female). Patients typically had numerous comorbidities, and many were treated with polypharmacy. Mean annual expenditures on total pain‐related health care and total all‐cause health care, respectively, (in 2010 USD) were: $1, 632, $24, 740 for pDPN; $1, 403, $16, 579 for PHN; and $1, 635, $18, 320 for fibromyalgia. In age‐stratified analyses, pain‐related health care expenditures decreased as age increased. Conclusions The numerous comorbidities, polypharmacy, and magnitude of expenditures in this sample of Medicare supplemental‐insured patients with pDPN, PHN, or fibromyalgia underscore the complexity and importance of appropriate management of these chronic pain patients.